(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2001)
Brief overview of Armenia’s potential in supplementary ore and mineral resources, which could be extracted without significant capital investments from the industrial waists and mounds processing, sewerage treatment silt utilization as well as gold, titanium and other precious components’ gravel deposits exploitation, reveals that prospective investors’ attention should be focused on the mentioned above aspects. Thereupon, the works concerned with the Prikama’s potential technogene deposits of sand methodological evaluation undertaken at Perm University have exclusive importance and their results are proposed below.